PERAN DINAS SOSIAL KOTA PEKANBARU DALAM PENANGGULANGAN KEMSIKINAN UNTUK MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TAHUN 2023 - Sinurat, Ruth Evinora; Wasillah, Asiah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Poverty is an issue that attracts significant attention as it relates to various aspects of life, such as the quality of life of individuals. As one of the goals of the Sustainable Development Goals (SDGs), namely "no poverty," the government’s role is highly emphasized. The Social Affairs Office of Pekanbaru City, as the government agency responsible for addressing this issue, holds an important and strategic role in poverty alleviation in Pekanbaru. This study aims to examine the role of the Social Affairs Office of Pekanbaru City in poverty alleviation to achieve the SDGs in 2023. This research is a descriptive qualitative study, with data collected through interviews and documentation. The data analysis techniques include data presentation, data reduction, verification, and finally, drawing conclusions. The theory used in this study is the theory of government roles by Arif, which explains the government’s role through four indicators: the government as a regulator, facilitator, dynamizer, and catalyst. The results of the study show that the Social Affairs Office of Pekanbaru City has carried out its role in all four indicators. As a regulator, the office is involved in drafting local regulations and setting development directions in planning documents such as the Work Plan (Renja) and Strategic Plan (Renstra) of the Social Affairs Office of Pekanbaru City. As a facilitator, the office is responsible for data collection, verification, and validation of social assistance recipients, as well as providing assistance and a forum for public complaints. As a dynamizer, the office mobilizes Social Welfare Potential and Resources (SWPR), and as a catalyst, it optimizes the role of SWPR by providing training and evaluation. However, these roles have not been fully optimized. This is evident from the lack of training to improve the capacity of SWPR conducted by the Social Affairs Office, resulting in suboptimal services to the community. Keywords: Role, Poverty, Social Affairs Office of Pekanbaru City